Methods for the determination of antioxidant activity of plant extracts in vitro - Kukić-Marković, Jelena (Archives of Pharmacy, 2023)
Plants are rich sources of secondary metabolites that exhibit diverse biological and pharmacological effects. Some plant ingredients, primarily phenolics, have significant in vitro antioxidant activity, thus implicating their contribution to the maintenance of redox balance in the body. These potential antioxidant agents are structurally very diverse, having different mechanisms of antioxidant activity. Since there is a growing necessity to detect, develop and understand effective antioxidant compounds, interest in the identification and the measurement of antioxidants in various plant isolates is persistently growing and many methods are being established. Most of the available in vitro tests are affordable and easy to perform, but due to the complex composition of plant extracts, different kinetics, mechanisms and specificity of the chemical reactions underlying these tests, there is no universal parameter for assessment of antioxidant activity. In this work, some of the currently most used in vitro methods for investigating and evaluating antioxidant activity of plant extracts are presented, emphasizing their advantages and weaknesses.
Keywords: antioxidants; plant extracts; in vitro tests